Chidamide and mitomycin C exert synergistic cytotoxic effects against bladder cancer cells in vitro and suppress tumor growth in a rat bladder cancer model. (1st April 2022) - Wang, Shao-Chuan; Yu, Chia-Ying; Wu, Yao-Cheng; Chang, Ya-Chuan; Chen, Sung-Lang; Sung, Wen-Wei
Abstract: Intravesical instillation (IVI) of Bacillus Calmette-Guerin (BCG) can prevent bladder cancer recurrence, but this agent has been out of stock in recent years. IVI of other agents, like chidamide, a histone deacetylase (HDAC) inhibitor, may have the potential to exert a therapeutic effect against bladder cancer by modifying the gene expression profiles associated with histone modifications that occur during cancer tumorigenesis. Here, we investigated the in vitro therapeutic effect of chidamide and/or mitomycin C in bladder cancer cell lines and screened related molecular pathways using an antibody array. We also quantitatively analyzed the synergistic effect of IVI of chidamide and mitomycin C in vivo in an N-methyl-N-nitrosourea (MNU)-induced rat bladder cancer model. The synergistic cytotoxic effect of chidamide plus mitomycin C was confirmed in both T24 and UMUC3 cells, with significantly greater induction of apoptosis elicited with chidamide plus mitomycin C than with either drug alone. The antibody array identified the Axl signaling pathway as the key target of the synergistic effect. Expression of Axl and its related downstream molecules, including claspin and survivin, was significantly suppressed. In the rat bladder cancer model, IVI of chidamide plus mitomycin C reduced tumor burden (Ki67 index) to a greater extent than either drug alone. Our results suggest that chidamide and mitomycin act synergistically to reduce MNU-induced bladder cancer. These findings provide new insights into a new and potentially effective approach to treating bladder cancer. Graphical abstract: Image 1 Highlights: This is the first study focus on intravesical instillation of chidamide in bladder cancer. Chidamide has the potential to exert a therapeutic effect with MMC in bladder cancer. AXL signaling might be the key target of the synergistic effect of Chidamide and MMC. In vivo, intravesical instillation of chidamide plus mitomycin C reduced tumor burden. Chidamide plus mitomycin act synergistically to reduce MNU-induced bladder cancer.